Chemical Compositions and Properties of Alkali Pickled Egg (Pidan) as Affected by Cations and Selected Pickling Ingredients - Palanivel Ganesan (Prince of Songkla University, 2016)
Thesis (Ph.D., Food Science and Technology)--Prince of Songkla University, 2010